Comparison of Arthroscopic versus Open Placement of the Fibular Tunnel in Posterolateral Corner Reconstruction - Krause, Matthias; Weiss, Sebastian; Kolb, Jan Philipp; Schwartzkopf, Ben; Frings, Jannik; Püschel, Klaus; Cavaignac, Etienne; Sonnery-Cottet, Bertrand; Frosch, Karl-Heinz (The Journal of Knee Surgery, 2022)
Introduction Precise fibular tunnel placement in posterolateral corner (PLC) reconstruction is crucial in restoring rotational and lateral stability. Despite the recent progress of arthroscopic PLC reconstruction techniques, landmarks for arthroscopic fibular tunnel placement and a comparison to open tunnel placement have not yet been described. This study aimed to (1) identify reasonable soft-tissue and bony landmarks, which can be identified by either arthroscopy, fluoroscopy, or open surgery in anatomic fibular tunnel placement and (2) to compare accuracy and reliability of arthroscopic fibular tunnel placement with open surgery.Materials and Methods In a retrospective study, 41 magnetic resonance images (MRIs) of the knee were analyzed with emphasis on distances of an ideal anatomic fibular tunnel to 11 soft-tissue and bony landmarks. Subsequently, in eight cadaver knees, the ideal fibular tunnel was created arthroscopically and with a standard open technique from antero-latero-inferior to postero-medio-superior with a 2-mm K-wire. Positions of both tunnels were compared on postinterventional computed tomography scans.Results Based on MRI measurements, the anatomic tunnel entry should be 14.50 (±2.18) mm distal to the tip of the fibular styloid and 10.76 (±1.37) mm posterior to the anterior edge of the fibula. The anatomic fibular tunnel exit was located 12.89 (±2.35) mm below the tip of the fibular head. Arthroscopic fibular tunnel placement was reliable in all cases. Instead, in five out of the eight cases with open surgery, the fibular tunnel crossed the defined safety distance to the closest cortical edge/tibiofibular joint (distance < 8 mm).Conclusions Reliable soft-tissue and bony landmarks of the fibular head allow arthroscopic anatomic fibular tunnel placement in PLC surgery, which shows a lower risk of tunnel malposition compared with open surgical techniques. Future studies will have to show whether clinical results of arthroscopic PLC reconstruction are in line with this study's technical results.Level of Evidence Level III.
Keywords: posterolateral corner; anatomic reconstruction; soft-tissue and bony landmarks; fibular tunnel